2011
DOI: 10.1111/j.1365-2842.2010.02142.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of partial implant-supported restorations on chewing side preference

Abstract: This study aimed at determining whether the individual's chewing side preference is affected by local effects, produced by the presence of implant-supported restorations. The test group included 81 patients with partial implant-supported prosthesis. The control group included 108 subjects with no implants. All subjects went through a series of laterality tests for chewing and tasks (hand, foot, eye and ear) side preference. The preferred chewing side (PCS) was determined by observing the first stroke of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 14 publications
(18 reference statements)
6
39
0
2
Order By: Relevance
“…It was expected, therefore, that they would have difficulty moving a bolus from one side of the mouth to the other and would therefore be more likely to chew on one side, and this preference tends to disappear with age [4,19,20]. The prevalence of CSP in subjects with permanent teeth (76%) is similar to the findings of Christensen and Radue [1], Pond et al [2], Kazazoglu et al [3], Varela et al [7], Nissan et al [17], Reinhardt et al [12], Martinez-Gomis et al [8] , Nissan et al [18], who reported prevalence of CSP, respectively: 68%, 77.8%, 88%, 88.4%, 97.4%, 78%, 63.24% and 97.9%.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It was expected, therefore, that they would have difficulty moving a bolus from one side of the mouth to the other and would therefore be more likely to chew on one side, and this preference tends to disappear with age [4,19,20]. The prevalence of CSP in subjects with permanent teeth (76%) is similar to the findings of Christensen and Radue [1], Pond et al [2], Kazazoglu et al [3], Varela et al [7], Nissan et al [17], Reinhardt et al [12], Martinez-Gomis et al [8] , Nissan et al [18], who reported prevalence of CSP, respectively: 68%, 77.8%, 88%, 88.4%, 97.4%, 78%, 63.24% and 97.9%.…”
Section: Discussionsupporting
confidence: 76%
“…Hoogmartens and Caubergh [16] observed that 56.25% of subjects (permanent dentition) realized the first chewing cycle on the right side, 31.25% on the left side and 12.5% had rates equal to the left and right sides. Nissan et al [17] and Nissan et al [18] observed that, respectively, 73% and 78.3% of the subjects had first cycle masticatory on the right side and 27% and 19.1% on the left side. Our results corroborate the results of these researches, because there is higher prevalence of preferred right side in the first chewing cycle, regardless of the dentition evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…they have a preferred chewing side (PCS). [5][6][7] The proportion of children or adults with a PCS ranges from 45% to 98%, [7][8][9][10][11] and there is no agreement on whether the right side is used more frequently than the left side. [8][9][10]12,13 Furthermore, it still unknown whether the PCS is centrally determined or related to peripheral factors, nor which peripheral factors are most closely related to the PCS.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10]12,13 Furthermore, it still unknown whether the PCS is centrally determined or related to peripheral factors, nor which peripheral factors are most closely related to the PCS. 7,10,11 Although natural foods can be used to assess masticatory function, artificial test food can be easily standardised and its physical properties remain the same over time. 14 Consequently, the use of artificial test foods such as silicon impression material is Page 5 of 20 A c c e p t e d M a n u s c r i p t 5 reliable.…”
Section: Introductionmentioning
confidence: 99%